Assessment of Body Image Distress in Women with Polycystic Ovarian Syndrome - Salma Zaman, Saira Yunus, Uzma Asif, Khadija Noor, Rabia Hayat, Gul-e Raana, Anosha Khan, Khaula Noor, Misha Khan, (Pakistan Journal of Medical & Health Sciences, 2023)
Background; Polycystic ovary syndrome (PCOS) is one of a common hormonal issue among women of childbearing age. Multiple cysts formation in ovaries, high level of androgen hormone and lack of ovulation and abnormal body appearance could be symptoms of PCOS that leads of severe negative effects on women mental health. Objective: To find out the association of body-appearance and mental health with PCOS. Study Design: Prospective cross-sectional study Place and Duration of Study: Department of Obstetrics & Gynaecology, Services Institute of Medical Sciences Lahore from 1st July 2022 to 31st December 2022. Methodology: This was questionnaire base study in which 54 PCOS suffering women and 67 control females were participated. Questions were asked about their body-image satisfaction and behavior towards sexual activities in routine life. Results: Average age in years of PCOS patients was 37.3±17.2 and control group was 44.8±13.7, average weight was 88.6±23.9 kg and 79.5±17.2 kg respectively. All were married and more than 60% of them were housewives. 9 questions were asked related to body image of PCOS patients and 63% of them were not feeling depressed about their physical appearance while only 13% were very much concerned and not satisfied with their physical appearance. Conclusion: Although PCOS has some negative effects on body appearance due to increased androgen level that might has some impact on self-confidence and less satisfaction with routine sexual life end up with depression and anxiety or some other mental disturbances, but there was no significant association was found between PCOS body-image and mental health. Keywords: Assessment, Body image distress, Polycystic ovarian syndrome